Genome Architecture Facilitates Phenotypic Plasticity in the Honeybee (Apis mellifera). (5th April 2020) - Duncan, Elizabeth J; Leask, Megan P; Dearden, Peter K
Abstract: Phenotypic plasticity, the ability of an organism to alter its phenotype in response to an environmental cue, facilitates rapid adaptation to changing environments. Plastic changes in morphology and behavior are underpinned by widespread gene expression changes. However, it is unknown if, or how, genomes are structured to ensure these robust responses. Here, we use repression of honeybee worker ovaries as a model of plasticity. We show that the honeybee genome is structured with respect to plasticity; genes that respond to an environmental trigger are colocated in the honeybee genome in a series of gene clusters, many of which have been assembled in the last 80 My during the evolution of the Apidae. These clusters are marked by histone modifications that prefigure the gene expression changes that occur as the ovary activates, suggesting that these genomic regions are poised to respond plastically. That the linear sequence of the honeybee genome is organized to coordinate widespread gene expression changes in response to environmental influences and that the chromatin organization in these regions is prefigured to respond to these influences is perhaps unexpected and has implications for other examples of plasticity in physiology, evolution, and human disease.